Beyond Clicks to Bricks: Studying the Impact of Webrooming on High-Involvement Appliance Purchases of Millennials - Karlvin Chester Vallejos; Samuel Sebastian Santos (SEISENSE Business Review)
Webrooming is a two-part shopping process where consumers research online before purchasing in-store. Anchored in Icek Ajzen's Theory of Planned Behavior, this study explores the webrooming trend in the high-involvement appliance category, including items such as televisions, refrigerators, air-conditioning units, and washing machines. Building on Eugene et al.'s (2021) investigation into consumers' tactile preferences, this research adds High Involvement Appliances as a moderating factor. The study employs purposive sampling, collecting data from 100 respondents aged 26-45 (Millennials) residing in Bulacan, Laguna, Cavite, and Rizal who have previously engaged in webrooming. The findings indicate that high-involvement appliances do not significantly moderate the relationships between Attitude, Subjective Norms, and Perceived Behavioral Control with the Intention to Webroom. This insight is crucial for both online and physical retailers, as it highlights the importance of understanding millennials' unique preferences and behaviors regarding high-involvement appliances. It also examines factors affecting this trend, potentially reshaping marketing strategies in the sector. Additionally, the study underscores the significance of an omnichannel approach, integrating online and offline touchpoints to enhance the shopping experience. The study aims to provide actionable insights for small- and medium-sized enterprises in the appliance sector, focusing on how millennials in the neighboring provinces of Metro Manila are influenced by webrooming before making high-involvement appliance purchases.